An In Vitro Study on the Antioxidant Properties of Cistus incanus Extracts - Małgorzata Olszowy-Tomczyk; Dorota Wianowska (Agriculture)
This paper concerns the evaluation of the antioxidant activity (AA) of extracts obtained from cistus herbs grown in Albania and Turkey. The extracts were prepared in a Soxhlet apparatus, as well as by the maceration and infusion methods, similar to the home method of preparing herbal teas. AA was determined using the DPPH (2,2′-diphenyl-1-picrylhydrazyl), ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), FRAP (ferric reducing antioxidant power) and β-carotene methods. It was proven that the AA of extracts depends not only on the extraction technique and AA assessment method but also on the place of plant cultivation. The smallest activity was determined using the β-carotene bleaching method, while the highest values were obtained using the FRAP method. On the other hand, the ABTS method showed a greater activity of the Albanian herb prepared using the Soxhlet technique. In addition, the antioxidant properties of extracts were compared with those of rutin standard solutions, showing that this characteristic component of cistus is not the only one that determines AA of extracts. As a result, the rutin content is not an indicator of the antioxidant properties of extracts. The other polyphenolic compounds, although occurring at lower concentration levels compared to rutin, modify the resultant AA of extracts. These studies confirmed the biological activity of cistus as a valuable source of polyphenolic compounds in the human diet.